The First Molecular Detection of Theileria luwenshuni from Haemaphysalis mageshimaensis on Orchid Island, Taiwan, with No Evidence of SFTSV - Pai-Shan Chiang; I-Jung Tsai; Yuan-Wei Hu; Hung-Jui Chen; I-Jen Chen; Hwa-Jen Teng; Shiu-Ling Chen (Pathogens)
Theileriosis is considered an economically important disease that may decrease productivity and cause a high mortality rate in livestock. Only a few studies have reported Theileria spp., such as T. sergenti and T. buffeli, in recent decades in Taiwan. In the present study, 401 ticks have been collected on Orchid Island in June 2022 and April 2023. Our environmental investigation for SFTSV unintentionally discovered T. luwenshuni in Haemaphysalis mageshimaensis on Orchid Island via PCR. The PCR products were sequenced, and the detected 18S rRNA gene sequences shared a 99.65–99.93% identity with T. luwenshuni sequences from ticks and ruminants in Myanmar and China. Despite the difficulty in clarifying the source of T. luwenshuni within neighboring regions, our findings provide an updated distribution of T. luwenshuni in Asia. This is not only the first time that T. luwenshuni was found in H. mageshimaensis but also the first report of T. luwenshuni on Orchid Island, Taiwan. Our study indicates that ruminants may be at risk of infection. Therefore, further investigations are needed to determine the distribution of T. luwenshuni among ruminants on Orchid Island and in Taiwan.